(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article examines the features of the artistic language of the novel "Treasure of Ulugbek" by the People’s Writer of Uzbekistan Odil Yaqubov. In particular, it is justified that the speech of Mirzo Ulug’bek is not only a historical reality, but also a tool for analyzing the inner world and psyche of the protagonist. At the same time, it has been proven that artistic speech is a methodological indicator that shows the skill of a writer